2015
DOI: 10.5897/jmpr2015.5844
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial activities of pomegranate extract against standard microorganisms of bovine mastitis

Abstract: Bovine mastitis is characterized by inflammation of the mammary gland, usually due to bacterial infection, compromising quantity and quality of milk production. This study aimed to determine the antibacterial activity, in vitro, of the hydroalcoholic extract of the pomegranate peel at 10% against standard strains of bovine mastitis. The colonies were adjusted to the concentration of 10 7 mL -1 using UV-visible spectrophotometry, and the extracts were evaluated in quintuplicate in concentrations of 1000, 500, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…The authors of [ 101 ] studied the DPPH IC50 values of water and ethyl acetate extracts of pomegranate seeds, fruits, and peels and reported an IC50 value of 15,100 mg dry weight/mL for the pomegranate seed ethyl acetate extract. The authors of [ 102 ] investigated the pomegranate fruits’ extracts and observed an antioxidant activity of 64.9%.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of [ 101 ] studied the DPPH IC50 values of water and ethyl acetate extracts of pomegranate seeds, fruits, and peels and reported an IC50 value of 15,100 mg dry weight/mL for the pomegranate seed ethyl acetate extract. The authors of [ 102 ] investigated the pomegranate fruits’ extracts and observed an antioxidant activity of 64.9%.…”
Section: Discussionmentioning
confidence: 99%